THE METHODOLOGY OF FORMING NATURAL-SCIENTIFIC CONCEPTS IN TEACHING NATURAL SCIENCES - Madina Khalimova (American Journals, 2024)
This article includes the analysis of theoretical and practical projects on Science subjects taught in primary classes in Uzbekistan. It demonstrates the unique aspects of forming a scientific worldview in students through physical concepts in the natural sciences (Science) textbook. It also highlights the process of mastering elementary physical concepts and developing the ability to apply this knowledge in familiar and unfamiliar situations, as well as in practical contexts.
Keywords: Natural science, competence, intellectual capacity, integration, project work, scientific awareness, initiative, creativity, tendency, XXI century skills.